2019
DOI: 10.1021/acs.chemrestox.9b00088
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bulky DNA Adducts by Non-Enzymatic Production of 1,2-Naphthoquinone-Epoxide from 1,2-Naphthoquinone under Physiological Conditions

Abstract: Quinones may be formed metabolically or abiotically from environmental pollutants and polycyclic aromatic hydrocarbons (PAHs); many are recognized as toxicological intermediates that cause a variety of deleterious cellular effects including mutagenicity. The PAH-o-quinone, 1,2-naphthoquinone (1,2-NQ), may exert its genotoxic effects through interactions with cellular nucleophiles such as DNA, however, the mechanisms of 1,2-NQ adduct formation are still under investigation. With the aim to further understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This is a well-recognized indicator of mutagenicity and is often used as a structural alert for mutagenicity . SHBint3 tends to select molecules with ortho-oxygen groups, which can also be mutagenic. ,,, TDB8r is the 3D topological distance-based autocorrelation, lag 8, weighted by a covalent radius. Lag refers to how close the atoms are together in the molecular structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a well-recognized indicator of mutagenicity and is often used as a structural alert for mutagenicity . SHBint3 tends to select molecules with ortho-oxygen groups, which can also be mutagenic. ,,, TDB8r is the 3D topological distance-based autocorrelation, lag 8, weighted by a covalent radius. Lag refers to how close the atoms are together in the molecular structure.…”
Section: Resultsmentioning
confidence: 99%
“…AATSC4m is the average autocorrelation, lag 4, weighted by atomic mass. This descriptor tends to highlight molecules with oxygen groups close together on a molecule’s perimeter which, like the epoxide group, tends to be a mutagenic substructure. , TDB1i, the 3D topological distance based autocorrelation, lag 1, is the highest for molecules with more oxygens close or on the molecule rings and lower for molecules without oxygens or with them on aliphatic chains. AATSC5c, the average centered Broto–Moreau autocorrelation, lag 5, weighted by charge, indicates oxygen groups five atoms apart, such as para-oxygen groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, the same authors showed that the mediated-covalent interaction between CREB and 1,2-NQ through Cys-286 blocks the DNA binding activity of CREB, resulting in the repression of CREB-regulated genes [79]. Knowing that a variety of environmental pollutants, including 1,2-NQ (or its metabolites), may cause abnormal DNA methylation, which further disturbs gene expression [80][81][82][83], it is possible that due to the chemical nature of 1,2-NQ (and its metabolite) that displays cytotoxic and genotoxic properties. This could include increasing topoisomerase II-mediated doublestranded DNA scission [84,85] and non-enzymatic oxidative transformation of 1,2-NQ to form an intermediate PAH-epoxide, which covalently binds to DNA [80].…”
Section: Discussionmentioning
confidence: 99%